Radiation shielding properties of bi-ferroic ceramics added with CNTs. (November 2022) - Sayyed, M.I.; Hannachi, E.; Slimani, Y.; Khandaker, Mayeen Uddin; Elsafi, M.
Abstract: This study reports the structural and radiation shielding properties of bi-ferroic ceramics added with carbon nanotubes (CNTs). Three samples labeled C1, C2, and C3 were synthesized by the sol-gel process followed by the sintering step at high temperatures. The structural analysis showed a tetragonal structure for C1 ceramic sample and a cubic structure for C2, and C3 samples. The inclusion of the CNTs phase into the bi-ferroic ceramic phases induces a variation in the lattice constant and causes a shrinkage in the cell unit volume V. For the C1, C2, and C3 ceramics, the linear attenuation coefficient (LAC) was experimentally measured at nine energies in the range of 8.1 × 10 −2 - 1.41 MeV. At 8.1 × 10 −2 MeV, the LAC is 14.244, 15.763 and 16.837 cm −1 for C1–C3 ceramics. The LAC results demonstrated the importance of utilizing these ceramics for low-energy radiation shielding applications. From the half-value layer (HVL) results, we found that a layer with a small thickness can be used to reduce the intensity of the low-energy photons. At higher energy, a thicker layer is needed to reduce the number of photons that can penetrate the ceramics. Highlights: Synthesis of bi-ferroic ceramics added with carbon nanotubes by the sol-gel process. The addition of the CNTs phase affects the crystal structure of the prepared ceramics. Different radiation shielding parameters including LAC, HVL, and RPE were measured. The addition of CNTs improves the radiation shielding efficiency of bi-ferroic ceramics. The prepared ceramics can be effective for low-energy radiation shielding applications.